Expanding the Known Functional Repertoire of the Human Cytomegalovirus pp71 Protein - Robert F. Kalejta; Emily R. Albright (Frontiers in Cellular and Infection Microbiology, 2020)
The human cytomegalovirus pp71 protein is packaged within the tegument of infectious virions and performs multiple functions in host cells to prime them for productive, lytic replication. Here we review the known and hypothesized functions of pp71 in regulating proteolysis, infection outcome (lytic or latent), histone deposition, transcription, translation, immune evasion, cell cycle progression, and pathogenesis. We also highlight recent advances in CMV-based vaccine candidates informed by an improved understanding of pp71 function.